ANALISIS STRATEGI TRANSFORMASI DIGITAL DAN ADOPSI GREEN TECHNOLOGY DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF BERKELANJUTAN PADA INDUSTRI MANUFAKTUR: ANALISIS STRATEGI TRANSFORMASI DIGITAL DAN ADOPSI GREEN TECHNOLOGY - Aksan; Mandala Bakti; Ahmad Hamid (LPPM AMBKENDARI, 2026)
This study aims to analyze Digital Transformation Strategy and Green Technology Adoption in creating Sustainable Competitive Advantage in the manufacturing sector. Amidst global market pressures and increasingly stringent environmental regulations, companies are required to evolve their technology in line with sustainability principles. Using a quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis method, this study examines the relationship between digitalization, green technology, and organizational competitiveness.The results of the hypothesis testing demonstrate that Digital Transformation has a positive and significant impact on Competitive Advantage (0.342), with the integration of Big Data Analytics and automation key to reducing operational inefficiencies. Further findings indicate that Green Technology Adoption is a stronger predictor of Competitive Advantage (0.458). This confirms that the market currently places a higher value on companies with a green brand image and the ability to implement cost efficiencies through zero-waste strategies. The most significant finding in this study is the influence of Digital Transformation on Green Tech Adoption, which recorded the highest coefficient of 0.512. This result confirms the Twin Transition concept, where digitalization functions as an intelligent infrastructure (such as IoT and Digital Twin) that enables the precise implementation of green technology.The study concludes that sustainable competitive advantage cannot be achieved through digitalization alone, but rather through strategic synergy between digital efficiency and a commitment to environmental sustainability. This synergy is the primary capital for companies to remain competitive in modern industrial competition.